Ablation of the P21 Gene of Trypanosoma cruzi Provides Evidence of P21 as a Mediator in the Control of Epimastigote and Intracellular Amastigote Replication - Teixeira, Thaise Lara; Chiurillo, Miguel Angel; Lander, Noelia; Rodrigues, Cassiano Costa; Onofre, Thiago Souza; Ferreira, Éden Ramalho; Yonamine, Camila Miyagui; Santos, Júlia de Gouveia; Mortara, Renato Arruda; da Silva, Claudio Vieira; Silveira, José Franco da (Frontiers in Cellular and Infection Microbiology, 2022)
P21 is an immunomodulatory protein expressed throughout the life cycle of Trypanosoma cruzi, the etiologic agent of Chagas disease. In vitro and in vivo studies have shown that P21 plays an important role in the invasion of mammalian host cells and establishment of infection in a murine model. P21 functions as a signal transducer, triggering intracellular cascades in host cells and resulting in the remodeling of the actin cytoskeleton and parasite internalization. Furthermore, in vivo studies have shown that P21 inhibits angiogenesis, induces inflammation and fibrosis, and regulates intracellular amastigote replication. In this study, we used the CRISPR/Cas9 system for P21 gene knockout and investigated whether the ablation of P21 results in changes in the phenotypes associated with this protein. Ablation of P21 gene resulted in a lower growth rate of epimastigotes and delayed cell cycle progression, accompanied by accumulation of parasites in G1 phase. However, P21 knockout epimastigotes were viable and able to differentiate into metacyclic trypomastigotes, which are infective to mammalian cells. In comparison with wild-type parasites, P21 knockout cells showed a reduced cell invasion rate, demonstrating the role of this protein in host cell invasion. However, there was a higher number of intracellular amastigotes per cell, suggesting that P21 is a negative regulator of amastigote proliferation in mammalian cells. Here, for the first time, we demonstrated the direct correlation between P21 and the replication of intracellular amastigotes, which underlies the chronicity of T. cruzi infection.